Configuration analysis of crop-pollination service management: a novel insight from the theory of planned behavior - Hongkun Zhao; Yaofeng Yang; Yajuan Chen; Huyang Yu; Zhuo Chen; Zhenwei Yang (PLoS ONE, 2025)
As the crisis of crop-pollination service increasingly gains global attention, improving crop-pollination service management (CPSM) has become a key challenge to achieve sustainable agriculture and safeguard food supply. Given that farmers are directly responsible for making decisions and managing agriculture, strategies for promoting CPSM should consider their perceptions, knowledge and role in enhancing pollination. A survey of 267 randomly selected smallholder farmers in Dengkou County was conducted to create and evaluate an integrated index for assessing on-farm pollination management among farmers, and to explore how key factors, grounded in the extending the theory of planned behavior (TPB), can influence their CPSM behaviors. The data is analyzed by using regression analysis, necessary condition analysis, fuzzy-set qualitative comparative analysis (NCA-fsQCA), and independent sample T test, and the findings reveal that education level and agricultural acreage are positively correlated with CPSM; there are three causal configurations to enhance CPSM: AT & PBC path, AT & Economic Incentive path, and PBC & Economic Incentive path; the contrasting effects of antecedent variables on different groups of principles of CPSM; the optimal state of CPSM requires at least Economic Incentive $1900.27. The findings provide practical implications for enhancing CPSM among different farmers through multi-pathways. This study can help to formulate CPSM strategies and increase farmers’ participation in pollinator-supporting behaviors in actual agricultural cultivation.